2024
DOI: 10.22581/muet1982.2401.2806
|View full text |Cite
|
Sign up to set email alerts
|

An IoT and machine learning solutions for monitoring agricultural water quality: a robust framework

Mushtaque Ahmed Rahu,
Muhammad Mujtaba Shaikh,
Sarang Karim
et al.

Abstract: All living things, comprising animals, plants, and people require water to survive. The world is covered in water, just 1 percent of it is fresh and functional. The importance and value of freshwater have increased due to population growth and rising water demands. Approximately more than 70 percent of the world's freshwater is used for agriculture. Agricultural employees are the least productive, inefficient, and heavily subsidized water users in the world. They also utilize the most water overall. Irrigation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Rahu et al [6] emphasized that monitoring water quality is a crucial task that guarantees the safety and usability of water resources. They also considered that traditional water quality monitoring techniques take a long time, are expensive, may not be accurate, and often do not produce real-time data.…”
Section: Use Of Ai For Water Quality Evaluationmentioning
confidence: 99%
See 2 more Smart Citations
“…Rahu et al [6] emphasized that monitoring water quality is a crucial task that guarantees the safety and usability of water resources. They also considered that traditional water quality monitoring techniques take a long time, are expensive, may not be accurate, and often do not produce real-time data.…”
Section: Use Of Ai For Water Quality Evaluationmentioning
confidence: 99%
“…They observed that, in the context of groundwater quality prediction, multiple linear regression (MLR) and artificial neural network (ANN) models stood out, with the ANN consistently outperforming MLR. Rahu et al [6] noted that several research studies have been conducted to investigate the use of ML algorithms in monitoring agricultural water quality. They concluded that deep learning algorithms outperform conventional regression models in terms of accuracy.…”
Section: Use Of Ai For Water Quality Evaluationmentioning
confidence: 99%
See 1 more Smart Citation